The fair corporate tax system in a global scenario: a pending question - Soler Roch, María Teresa (2018)
The traditional International Taxation standards do not grant a fair corporate tax system, especially in the case of multinational groups operating in a global scenario. The crisis of the principle of global taxation as well as tax competition between tax jurisdictions, provide opportunities for tax planning in the hands of these taxpayers. OECD BEPS Action Plan and similar proposals launched by the European Union, mean some significant steps in this direction, but the fairness of the system is still a pending question and a new benchmark becomes necessary in order to go beyond the domestic scope of the ability to pay principle.